2020
DOI: 10.3390/jcm9061648
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers of Robotic Colonoscopy: A Comprehensive Review of Robotic Colonoscopes and Technologies

Abstract: Flexible colonoscopy remains the prime mean of screening for colorectal cancer (CRC) and the gold standard of all population-based screening pathways around the world. Almost 60% of CRC deaths could be prevented with screening. However, colonoscopy attendance rates are affected by discomfort, fear of pain and embarrassment or loss of control during the procedure. Moreover, the emergence and global thread of new communicable diseases might seriously affect the functioning of contemporary centres performing gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 160 publications
0
66
0
Order By: Relevance
“…The limitations of traditional endoscopes have led to the conceptualization of new robotic solutions. Some of them use electromechanical actuation (e.g., the NeoGuide endoscopy system and the Invendoscope [ 9 ]), some use electropneumatic actuation (e.g., the Aer-O-Scope system [ 10 ], the ColonoSight [ 11 ], and the Endotics system [ 1 , 2 ]), some use magnetic actuation (e.g., the SUPCAM [ 12 ]), while some are still under development; comprehensive literature reviews with comparative and detailed analyses are reported in [ 13 , 14 , 15 ]. The Endoo European project [ 16 ], enabled by previous works [ 17 , 18 , 19 , 20 , 21 ], was conceived to design an innovative robotic system able to reduce the invasiveness of CC.…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of traditional endoscopes have led to the conceptualization of new robotic solutions. Some of them use electromechanical actuation (e.g., the NeoGuide endoscopy system and the Invendoscope [ 9 ]), some use electropneumatic actuation (e.g., the Aer-O-Scope system [ 10 ], the ColonoSight [ 11 ], and the Endotics system [ 1 , 2 ]), some use magnetic actuation (e.g., the SUPCAM [ 12 ]), while some are still under development; comprehensive literature reviews with comparative and detailed analyses are reported in [ 13 , 14 , 15 ]. The Endoo European project [ 16 ], enabled by previous works [ 17 , 18 , 19 , 20 , 21 ], was conceived to design an innovative robotic system able to reduce the invasiveness of CC.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, screening programs have already been or will be impeded in the near future by several psychosocial, and healthcare-related factors, 6 including between others: (i) risk of disease transmission, eg, coronavirus disease 19 (COVID-19); 7 (ii) inadequate number of skilled healthcare professionals; 8 (iii) long learning curves to achieve full professional experience in endoscopic techniques; 9 (iv) increasing numbers of physicians/nurses with burnout syndromes; 10,11 (v) increasing number of "need-to-screen" individuals worldwide; 12 and more importantly, (vi) patients' perspective and concerns on colonoscopy-based CRC screening (eg, unpleasant preparation, pain, cost) and/or potential to choose other non-invasive options. 13,14 Several investigators have attempted through surveys and questionnaires to document attitudes towards colonoscopy as well as possible concerns about the nature, adverse events, and receptiveness of the procedure. 15,16 The invasive nature of the procedure, the effects of the laxative bowel preparation, and the fear of discomfort/pain or embarrassment seem to stand out among others.…”
Section: Introductionmentioning
confidence: 99%
“…For intelligent navigation of the lumen by an endoscope, both the highly malleable shape of the gut and the position of the camera must be estimated together, which remains a challenge to the engineering community. 84 Although simple surgical tasks have been successfully automated through AI, these as yet are not safely achievable on deformable tissue. This is a rapidly evolving field, and the continuing advancement of AI-driven endoluminal techniques should be expected both in navigation and in therapeutics.…”
Section: Futurementioning
confidence: 99%